Pengaruh Konsentrasi Zat Giberelin (GA3) Terhadap Perkecambahan Biji Cendana (Santalum album Linn.) - Angriani Noventa Tefa; Wilhelmina Seran; Astin E. Mau; Roni Sipayung (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
There are two factor s that affect the success of sandalwood plant breeding, namely, the presence of host plants needed by sandalwood plants and the treatment of sandalwood seeds. This study aims to determine how the concentration of gibberellin (GA3) on sandalwood seed germination and which concentration treatment has the most effect on sandalwood seed germination. The method used in this study was a Complete Randomized Design (RAL) with gibberellin concentration treatment (GA3) consisting of A0 = 0% (Immersion in aquades (control)), A1 = 70% (1,000 mL aquades + 0.70 grams (GA3)), A2 = 75% (1,000 mL aquades + 0.75 grams (GA3)), A3 = 80% (1,000 mL aquades + 0.80 grams (GA3)), A4 = 85% (1,000 mL aquades + 0.85 grams (GA3)), A5 = 90% (1,000 mL aquades + 0.90 grams (GA3)). The results showed that the variation in the concentration of gibberellins (GA3) 70%, 75%, 80%, 85% and 90% in sandalwood plants had a significant effect on all parameters and the use of GA3 with A5 = 90% treatment (1,000 mL aquades +0.90 grams (GA3)) gave the best value and had a real effect on four parameters, namely germination rate with an average of 36%, germination rate of 44% (12MST), wet weight of 0.31 grams, and dry weight of 0.13 grams.